The influence of flexibility on the formation of basic taekwondo techniques in children aged 10–12 years - Milyaeva, Karolina R.; Akindinova, Marina M. (Физическое воспитание и студенческий спорт)
In the practice of preparing athletes for high-level competitions, special physical training is of great importance, namely the application of a variety of means and methods that are used in practice by high-level athletes in training before the competition. The article presents the results of a research conducted with the participation of students of the first year of study and more than one year of training in taekwondo, during which such methods as pedagogical observation, pedagogical experiment, testing method, methods of mathematical and statistical data processing were used. In the course of the study, it was revealed that the influence of flexibility education on the formation of basic taekwondo techniques in children aged 10–12 years is very important, since in taekwondo it is taken as the basis for blows to the head, and even blows to the body. The authors note that with reduced flexibility, athletes lose most of their strength during combat. Taking into account the data obtained, the possibility of planning the direction of loads, improving the quality of training and the need to pay more attention to stretching during training are shown.